A review of organic-inorganic hybrid clay based adsorbents for contaminants removal: Synthesis, perspectives and applications. Issue 5 (October 2021) - Gil, A.; Santamaría, L.; Korili, S.A.; Vicente, M.A.; Barbosa, L.V.; de Souza, S.D.; Marçal, L.; de Faria, E.H.; Ciuffi, K.J.
Abstract: Clay minerals are a very interesting platform for the development of novel functional materials. For years, there has been a growing interest in this field because clays offer different possibilities for the design of functional materials with various possible applications, such as adsorbents, drug delivery systems, catalysts, photocatalysts and nanocomposites. This review highlights mainly, but not only, tailored functionalized clay minerals containing amino groups, which are widely employed due to their simplicity and efficiency. Their use as adsorbents of several classes of water contaminants, including emerging organic pollutants, drugs, surfactants, pesticides, anions, and heavy metals, as well as of contaminants in the gaseous phase, namely CO2, is also reviewed, and removal strategies based on these amino-functionalized materials are presented. Graphical Abstract: ga1 Highlights: Synthesis of aminofunctionalized clay minerals as efficient adsorbents. Aminofunctionalized clay minerals as systems to clean water from emerging organic contaminants. Aminofunctionalized clay minerals as efficient adsorbents to removal anions and heavy metals. Aminofunctionalized clay minerals as adsorbents of CO2 .